Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1016/0306-4522(92)90222-n
|View full text |Cite
|
Sign up to set email alerts
|

The chromogranins A and B: The first 25 years and future perspectives

Abstract: Calcium-binding and aggregation properties of parathyroid secretory protein-1 (chromogranin A). Bone Min. 4, 17-25. GOK S. U., Hamilton J. W. and Cohn D. V. (1991) Sulfated secreted forms of bovine and porcine parathyroid chromogranin A (secretory protein-I). New suggestions for the physiological role of secretory protein-I. Bone Mm. 2, 251-255. Gorr S. U., Shioi J. and Cohn D. V. (1989) Interaction of calcium with porcine adrenal chromogranin A (secretory protein-I) and chromogranin B (secretogranin I). Am. J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
439
1
7

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 635 publications
(466 citation statements)
references
References 351 publications
19
439
1
7
Order By: Relevance
“…21,22 The CHGB gene encodes for chromogranin B, which belongs to a family of soluble proteins stored and released from large dense-core secretory vesicles at the synapse. 36,37 These granins have an important role in the sorting and aggregation of secretory products in the transGolgi network and in the subsequent formation of secretory granules. 38 A reduction of chromogranin B levels in cerebrospinal fluid (CSF), as well as chromogranin B-like immunoreactivity in distinct subregions of the hippocampus were reported in patients with SZ.…”
Section: Synapse and Neurotransmissionmentioning
confidence: 99%
“…21,22 The CHGB gene encodes for chromogranin B, which belongs to a family of soluble proteins stored and released from large dense-core secretory vesicles at the synapse. 36,37 These granins have an important role in the sorting and aggregation of secretory products in the transGolgi network and in the subsequent formation of secretory granules. 38 A reduction of chromogranin B levels in cerebrospinal fluid (CSF), as well as chromogranin B-like immunoreactivity in distinct subregions of the hippocampus were reported in patients with SZ.…”
Section: Synapse and Neurotransmissionmentioning
confidence: 99%
“…CGA is expressed in a wide variety of neuroendocrine cell types, each of which co-express a unique and cell-specific polypeptide hormone or neurotransmitter ( [1], and references therein). To achieve this co-expression the chromogranin gene must be able to respond to the wide variety of developmental and hormonal signals that drive polypeptide expression in each of these cell types (see Table 1).…”
Section: Structure Of the Cga Gene And Regulation Of Cga Gene Transcrmentioning
confidence: 99%
“…[1]. There are two difficulties in the assumption that CGA, CGB, or SglI need be abundant in all regulated secretory granules in all endocrine cells in order to play a role in granulogenesis in any of them.…”
Section: Chromogranin A: Aggregatory Properties and Their Relevance Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies consistently revealed stress-related downregulation 14) . CgA exists in various endocrine organs and its secretion is regulated by the SAM system 15,16) . In vitro experiments have also demonstrated that CgA exhibits antifungal and antibacterial properties 17,18) .…”
Section: ⅰ.Introductionmentioning
confidence: 99%